The Effect of Selenium, Zinc, and their Combined Supplementation on Cardiometabolic Biomarkers-comparing their Effects in the Energy Restriction and High-fat Diet Methods in Obese Rats - Hasani, Motahareh; Monfared, Vahid; Aleebrahim-Dehkordi, Elahe; Jafari, Ali; Agh, Fahimeh; Khazdouz, Maryam; Vahid, Farhad; Vafa, Mohammadreza (Current Molecular Medicine, 2024)
Introduction: The fat distribution in the body determines the risk of cardiometabolic problems such as heart disease and diabetes. Some dietary supplements, such as selenium and zinc, possess lipolytic and anti-angiogenic functions, which may be a useful strategy in reducing the risk of cardiometabolic complications. This study evaluated the effect of zinc (Zn), selenium (Se), and their combined supplementation on cardiometabolic risk factors in male Wistar rats in two nutritional models, including caloric restriction (CR) and high-fat diet (HFD). Methods and Materials: The 48 male Wistar rats were divided into three diet groups (HFD and CR and normal diet (ND)). The HFD group was subdivided into four groups (N=8 rats in each group) that received (HFD+Se), (HFD+Zn), (HFD+Zn+Se), and HFD alone as the control group, respectively. After 8 weeks of intervention, biochemical tests were performed on serum levels, including measurement of lipid profile (triglyceride, Cholesterol, LDL and HDL) and glycemic indices (fasting blood sugar, insulin and insulin sensitivity markers). Results: The results showed that supplementation significantly improved the lipid profile (P <0.001). A comparison of glucose homeostasis indices in the study groups also showed a significant difference. The serum level of glucose was higher in the HFD group than in the intervention groups (P <0.001). Also, the rate of improvement of lipid profile and glycemic indexes in the group receiving the combination of two supplements showed a better trend than those receiving zinc and selenium alone. However, the values were statistically significant only for glucose homeostasis indices (P <0.001). Conclusion: Although obesity is a multifactorial condition, controlling other risk factors, zinc and selenium and their combined supplementation can lead to promising solutions for the treatment of obesity-induced glucose and lipid homeostasis disorders.
Keywords: high-fat diet